The Effect of Capitation Value of Healthcare and Social Security Agency on Service Quality at Primary Clinics - Neny Nurlaily; Titik Ernawati; FaraValeyria Irma Zain; Chomariyah (Indian Journal of Forensic Medicine & Toxicology, 2021)
Indonesia started to apply the National Health Insurance System on January 1, 2014, and the legal entityformed to administer this program is the Healthcare and Social Security Agency. Funding for the Healthcareand Social Security Agency at primary clinic uses the capitation system where the funds are mostly used forservices and operations. The use of capitation funds at the primary clinic is fully managed by itself based onthe agreement. This actually creates the potential for fraud because of the lack of regulations on using thecapitation funds. Fraud at the primary clinic does not really appear on the surface like a fraud in hospitals. Itcan be in the form of insufficient resources, facilities and service discrimination. Many studies have showna link between capitation funds and health services. A primary clinic needs to have an audit team to evaluatewhether the use of capitation funds is following the expected targets and needs.